Multiliteracy and Work Readiness: The Central Role of Career Adaptability in the Digital Era - Dewantara, Hajar; Inanna, Inanna; Pahrul, Pahrul; Rahmi, Nur (Quantitative Economics and Management Studies, 2025)
Digital transformation has become a global phenomenon that fundamentally changes the competencies required of college graduates to enter the workforce. Therefore, the multiliteracy concept, encompassing entrepreneurial literacy, human literacy, and digital literacy, is a crucial indicator that can influence the work readiness of the younger generation. This study aims to analyze the model of student work readiness formation in the digital era through the role of career adaptability as a psychosocial mechanism that bridges the relationship. This study uses a quantitative approach with a questionnaire as a data collection technique. Furthermore, the data is processed using Structural Equation Modeling analysis. This study found that human literacy and digital literacy have a direct effect on work readiness. Furthermore, entrepreneurial literacy contributes to increased career adaptability. Meanwhile, career adaptability is a determinant that can strengthen the relationship between multiliteracy and work readiness, emphasizing the importance of adaptive capacity in facing professional dynamics in the digital era. The results of this study have implications for the importance of higher education institutions developing needs-based educational curricula oriented toward work readiness and Outcome-Based Education-based learning.